Controle da qualidade da tensão de fornecimento em redes secundárias de distribuição através de compensador estático de reativos - Melo, Vinícius Secchin de (2009)
This work deals with the implementation of voltage control techniques to improve the power quality in low voltage distribuition circuits. Some control techniques related to positive, negative and zero sequence components were implemented in order to mitigate voltage unbalances, voltage sags and also keep the steady-satate voltage in acceptable levels. This way, a real reactive power compensator, based on STATCOM architeture, was developed. The electrical and thermal protection of the developed equipament was implemented using a DSP device. Specific operations modes was defined to depict STATCOM control status. The initialization and parametrization it is made through a humam-machine interface where informations are showed about the operations modes, compensation in each fase and protection. Several simulation results and correlated analyses are presented for different technical conditions of the equipament operation. The major contribuitions represented by this work are the software implemention of the acquisitin procedure for voltage sequence components, based on dq0 trasnformation method, and also the construction of a STATCOM protype to be used in aerial low voltage distribuition circuits.